Impact Of English Proficiency On Employee Performance: A Systematic Review Of Workplace Studies - Umul Khoiriyah; Rizky Islamiyati Wilujeng; Fatimah Iefa Rusydiana Nursetyo (Proceedings Law, Accounting, Business, Economics and Language, 2025)
This study presents a Systematic Literature Review (SLR) that investigates the impact of English Language Proficiency (ELP) on employee performance across various workplace contexts. Contained on ten peer-reviewed articles published between 2010 and 2025, this review identifies patterns, contradictions, and research gaps in how English proficiency shapes job performance, communication, promotion, and organizational inclusion. Findings indicate that ELP significantly enhances productivity, team collaboration, and access to career opportunities, particularly in multinational or cross-cultural environments. However, many organizations still fail to provide sufficient training support, creating barriers for non-native speakers who experience psychological challenges such as communication anxiety and lack of confidence. Thematic analysis reveals that ELP is not only a tool for effective communication but also a symbol of global competence and professional credibility. Contradictions in the literature emerge regarding reliance on standardized English tests versus practical workplace fluency. Moreover, the review highlights a lack of longitudinal studies tracking ELP’s long-term effects on career progression and leadership. This study concludes that ELP should be treated as both a strategic asset and a developmental priority within organizational policies and employee training programs. The insights provided aim to guide HR professionals, educators, and policymakers in designing more inclusive, context-specific English training that aligns with global workforce demands. The review contributes to a deeper understanding of how language proficiency can influence economic and career outcomes in an increasingly English-dominated professional landscape.